Charge-product control approach to electrostatic leader-follower formations in LEO plasma wakes. Issue 11 (1st June 2021) - Maxwell, Jordan; Schaub, Hanspeter
Abstract: The feasibility of using electrostatic forces to stabilize a close-proximity leader-follower formation is investigated. The leader craft is equipped with a set of affixed spheres whose charge is modulated to hold the charged follower craft along a proscribed trajectory to its nominal leader-relative position. This charge structure and the follower craft are constrained to remain in the plasma wake generated behind all LEO craft because the more-dense ambient plasma outside the wake prevents object charging and electric field propagation. Once the formation is achieved, a controlled electric field is generated by the leader to counter relative accelerations from perturbations like differential drag and solar radiation pressure, holding the follow near its nominal position. Two controllers are derived for the system described, incorporating Coulomb accelerations and linearized gravity and drag accelerations. Simulations are run under unmodeled perturbations and sensor noise for different scenarios, demonstrating the challenges and benefits associated with electrostatic actuation.